Prevalência e fatores associados à constipação intestinal e aos outros transtornos evacuatórios no primeiro ano de vida - Caroline de Faria e Silva (2009)
Infant intestinal constipation is a common problem. A non-systematic literature review was performed on PUBMED, BIREME and SCIELO using the following key concepts: constipation, infant, epidemiology and risk factors. The term All Infant: birth-23 months was selected for the specific search. The prevalence of constipation varied from 0.7 to 48%. Criteria for the diagnosis of this disorder in infants are available but many authors adopt their own criteria, which may result in a large prevalence variation between the several studies conducted. With regards to the risk factors, it was observed that parents, brothers and uncles of the constipated children present the constitutional and hereditary components. Some studies have shown that the maternal breastfeeding is a protection factor against the constipation development. Researches have confirmed that the consumption of cows milk and formulas favor the occurrence of this event in the first year of life. There are few investigations made regarding the consumption of alimentary fibers by infants and, therefore, the utilization as a nutritional supplement is still controversial. The development of prevalence studies oriented specifically to infants with risk factors associated to constipation may provide a better comprehension of the morbosity impact of this disease as well as an improved treatment and prevention